A point-prevalence survey of healthcare-associated infection in fifty-two Chinese hospitals. Issue 1 (January 2017) - ,; Luo, Aiwu; Zhu, Binghua; Wang, Bo; Zhang, Bo; Wen, Chaoyang; Zhang, Guocong; Yang, Haiqing; Zhang, Hong; Zhai, Hongyan; Wang, Hui; Shi, Jieran; et al.
Summary: Background: Healthcare-associated infection (HCAI) represents a major problem for patient safety worldwide. Aim: To demonstrate the prevalence, causative agents, and risk factors for HCAI in Chinese hospitals. Methods: A one-day point-prevalence survey was conducted in 52 Chinese hospitals between October 2014 and March 2015. A web-based software system was developed for data entry and management. Findings: Among 53, 939 patients surveyed, the prevalence of patients with at least one HCAI was 3.7%. Of 2182 HCAI episodes, the most frequently occurring types were lower respiratory tract infections (47.2%), followed by urinary tract infection (12.3%), upper respiratory tract infection (11.0%), and surgical site infection (6.2%). The prevalence of patients with at least one HCAI in critical care units was highest (17.1%). Device-associated infections, including ventilator-associated pneumonia, catheter-associated urinary tract infection, and central catheter-associated bloodstream infection, accounted for only 7.9% of all HCAIs. The most frequently isolated micro-organisms were Pseudomonas aeruginosa [206 infections (9.4%)], Acinetobacter baumannii [172 infections (7.9%)], Klebsiella pneumoniae [160 infections (7.3%)], and Escherichia coli [145 infections (6.6%)]. Of the survey patients (18, 206/53, 939), 33.8% were receiving at least one antimicrobial agent at the time of the survey. Risk factors for HCAI included older age (≥80 years), male gender, days of hospital admission, admission into a critical care unit, and device utilization. Conclusion: Our study suggests that the overall prevalence of HCAI in surveyed Chinese hospitals was lower than that reported from most European countries and the USA. More attention should be given to the surveillance and prevention of non-device-associated HCAI in China.